Solution2

# Solution2 - SOLUTIONS FOR HOMEWORK 2 3 According to the...

This preview shows pages 1–2. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: SOLUTIONS FOR HOMEWORK 2 3. According to the definition of E , F and G , we have E = { ( i, j ) | i + j = odd } = { (1 , 2) , (1 , 4) , (1 , 6) , (2 , 1) , (2 , 3) , (2 , 5) , (3 , 2) , (3 , 4) , (3 , 6) , (4 , 1) , (4 , 3) , (4 , 5) , (5 , 2) , (5 , 4) , (5 , 6) , (6 , 1) , (6 , 3) , (6 , 5) } , F = { ( i, j ) | i = 1 or j = 1 } = { (1 , 1) , (1 , 2) , (1 , 3) , (1 , 4) , (1 , 5) , (1 , 6) , (2 , 1) , (3 , 1) , (4 , 1) , (5 , 1) , (6 , 1) } , G = { ( i, j ) | i + j = 5 } = { (1 , 4) , (2 , 3) , (3 , 2) , (4 , 1) } . Therefore EF = { (1 , 2) , (1 , 4) , (1 , 6) , (2 , 1) , (4 , 1) , (6 , 1) } , E ∪ F = { (1 , 2) , (1 , 4) , (1 , 6) , (2 , 1) , (2 , 3) , (2 , 5) , (3 , 2) , (3 , 4) , (3 , 6) , (4 , 1) , (4 , 3) , (4 , 5) , (5 , 2) , (5 , 4) , (5 , 6) , (6 , 1) , (6 , 3) , (6 , 5) } , (1 , 1) , (1 , 3) , (1 , 5) , (3 , 1) , (5 , 1) } F G = { (1 , 4) , (4 , 1) } , EF c = { (2 , 3) , (2 , 5) , (3 , 2) , (3 , 4) , (3 , 6) , (4 , 3) , (4 , 5) , (5 , 2) , (5 , 4) , (5 , 6) , (6 , 3) , (6 , 5)...
View Full Document

## This note was uploaded on 04/13/2008 for the course M 362k taught by Professor Berg during the Spring '08 term at University of Texas.

### Page1 / 2

Solution2 - SOLUTIONS FOR HOMEWORK 2 3 According to the...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online